Health of the elderly: perspective of nursing - Guarda, Lenny Moreira da (2022)
The health of the elderly is provided by the Unified Health System (SUS) in force in the country, which ensures that from primary to secondary care the elderly is assisted by medicine through studied professionals and specialists in geriatrics, which includes the nursing team.In this sense, the research aimed to understand the role of nursing in the health of the elderly, so beyond the mastery of the professionals' techniques, it was possible to understand that it is necessary to be compressed by the guidelines, policies and psychosocial issues that permeate all human beings with subjective characteristics in aging. The results show that policies and actions are a good support in the performance of old age care, however more studies and continuing education are needed for nursing professionals in the care regarding the techniques of care, diagnosis and health promotion of the elderly.